A Framework for Software Preservation - Brian Matthews; Arif Shaon; Juan Bicarregui; Catherine Jones (International Journal of Digital Curation, 2010)
Software preservation has not had detailed consideration as a research topic or in practical application. In this paper, we present a conceptual framework to capture and organise the main notions of software preservation, which are required for a coherent and comprehensive approach.Â  This framework has three main aspects. Firstly a discussion of what it means to preserve software via a performance model which considers how a software artefact can be rebuilt from preserved components and can then be seen to be representative of the original software product. Secondly the development of a model of software artefacts, describing the basic components of all software, loosely based on the FRBR model for representing digital artefacts and their history within a library context. Finally, the definition and categorisation of the properties of software artefacts which are required to ensure that the software product has been adequately preserved. These are broken down into a number of categories and related to the concepts defined in the OAIS standard. We also discuss our experience of recording these preservation properties for a number of BADC software products, which arose from a series of case studies conducted to evaluate the software preservation framework, and also briefly describe the SPEQS toolkit, a tool to capture software preservation properties within a software development.